MALDI Imaging Analysis of Neuropeptides in Africanized Honeybee (Apis mellifera) Brain: Effect of Aggressiveness - Pratavieira, Marcel [UNESP]; Menegasso, Anally Ribeiro Da Silva [UNESP]; Esteves, Franciele Grego [UNESP]; Sato, Kenny Umino [UNESP]; Malaspina, Osmar [UNESP]; Palma, Mario Sergio [UNESP] (My University, 2018)
Aggressiveness in honeybees seems to be regulated by multiple genes, under the influence of different factors, such as polyethism of workers, environmental factors, and response to alarm pheromones, creating a series of behavioral responses. It is suspected that neuropeptides seem to be involved with the regulation of the aggressive behavior. The role of allatostatin and tachykinin-related neuropeptides in honeybee brain during the aggressive behavior is unknown, and thus worker honeybees were stimulated to attack and to sting leather targets hung in front of the colonies. The aggressive individuals were collected and immediately frozen in liquid nitrogen; the heads were removed and sliced at sagittal plan. The brain slices were submitted to MALDI spectral imaging analysis, and the results of the present study reported the processing of the precursors proteins into mature forms of the neuropeptides AmAST A (59-76) (AYTYVSEYKRLPVYNFGL-NH2), AmAST A (69-76) (LPVYNFGL-NH2), AmTRP (88-96) (APMGFQGMR-NH2), and AmTRP (254-262) (ARMGFHGMR-NH2), which apparently acted in different neuropils of the honeybee brain during the aggressive behavior, possibly taking part in the neuromodulation of different aspects of this complex behavior. These results were biologically validated by performing aggressiveness-related behavioral assays using young honeybee workers that received 1 ng of AmAST A (69-76) or AmTRP (88-96) via hemocele. The young workers that were not expected to be aggressive individuals presented a complete series of aggressive behaviors in the presence of the neuropeptides, corroborating the hypothesis that correlates the presence of mature AmASTs A and AmTRPs in the honeybee brain with the aggressiveness of this insect.
Keywords: agressivity; honeybee brain; MALDI imaging; mass spectrometry; neuropeptides; neuroproteomics